Klasterisasi Angka Usia Muda Melek TIK Berdasarkan Algoritma K-Means Menurut jumlah Provinsi Indonesia - Massie, Olivia Immanuela; Padilah, Tesa Nur (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Advances in technology that can’t be separated from human life, making information easier to obtain. The results of a survey conducted by APJII on the penetration of internet users in 2018 based on age, stated that the use of the internet was dominated by young people. For this reason, it is hoped that in the future there will be improvements in numbers in the form of equitable use of ICT in all provinces in Indonesia. This research was conducted based on the clustering of young people who are ICT literate. The amount of data used is in accordance with the current number of Indonesian provinces, which are thirty-four provinces using the K-Means algorithm. The dataset in this study was obtained from the official government website https://.www.bps.go.id/ from 2017 to 2019. Clustering was carried out only to group provinces into two types of groups, which can later be used as evaluation material for the government in the framework of the equitable distribution of ICT in each province. The final result of this study is that there are twenty-five provinces that are included in cluster 1 and nine provinces are included in cluster group 2. Thus it is necessary to increase the ICT literacy rate for provincial clusters whose values are still lagging behind other provinces.